ARBITRATION AND MEDIATION METHOD APPLIED TO ISLAMIC FINANCE CONFLICTS IN MALAYSIA (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
Malaysia has already known as an Islamic country. In a country of multi-ethnicity, multi-religion and multi-cultural societies, demands a concept of justice and equality that is different from other countries, particularly the ones with homogenous societies. The highest law of the land places Islam, the religion associated with one of the main ethnicity, as the official religion of the nation and allowed the duality of economic system, in particular banking system, whereby conventional banking system exists side-by-side with the Sharia-compliant, Islamic banking. By reviewing the pertinent literature on the development of Islamic banking, the reviewed cases on Islamic banking and its contributions to Malaysian society regardless of ethnicity and religion. The discussion in this paper therefore will be directed towards highlighting the laws and mechanisms of solution on Islamic banking and its implication to enhance the application of Islamic banking laws to consumers regardless of ethnicity and religion, in order to maintaining fairness and justice in a multi-ethnic society